2023
DOI: 10.1111/bjep.12624
|View full text |Cite
|
Sign up to set email alerts
|

Boarding versus day‐students: A mixed‐methods analysis of sleep and its relationship with psychological distress

Abstract: BackgroundBoarding students face unique challenges when entering school, including: adapting to a novel environment, where they are separated from family, friends and culture, for up to 40 weeks per year. A particular challenge is sleep. A further challenge is coping with the demands of boarding with its potential impact on psychological well‐being.AimsTo explore how boarders' sleep differs from that of their day‐student peers, and how this relates to psychological well‐being.Sample and Methods309 students (59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 121 publications
0
1
0
Order By: Relevance
“…In a study of children aged 17 years or younger, Tsao et al (2021) found that children who had insufficient sleep tended to have a lower flourishing index than children who had sufficient sleep, specifically, a lower level of curiosity and restlessness. Reardon et al (2023) reported that the flourishing score tends to be higher in adolescent students who sleep longer. In addition, Armand ( Armand et al, 2021 ) in a report on college students and Richter (2015) in a report on adults also report that sleep duration is positively correlated with psychological well-being.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of children aged 17 years or younger, Tsao et al (2021) found that children who had insufficient sleep tended to have a lower flourishing index than children who had sufficient sleep, specifically, a lower level of curiosity and restlessness. Reardon et al (2023) reported that the flourishing score tends to be higher in adolescent students who sleep longer. In addition, Armand ( Armand et al, 2021 ) in a report on college students and Richter (2015) in a report on adults also report that sleep duration is positively correlated with psychological well-being.…”
Section: Introductionmentioning
confidence: 99%